“As Long As I’m Me”: From Personhood to Personal Identity in Dementia and Decision-making - Toomey, James (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
As older people begin to develop dementia, we confront ethical questions about when and how to intervene in their increasingly compromised decision-making. The prevailing approach in bioethics to tackling this challenge has been to develop theories of “decision-making capacity” based on the same characteristics that entitle the decisions of moral persons to respect in general. This article argues that this way of thinking about the problem has missed the point. Because the disposition of property is an identity-dependent right, what matters in dementia and decision-making is an individual’s personal identity with their prior self, not their moral personhood. Therefore, in considering when and how we ought to intervene in the decision-making of those with dementia, we must look to the philosophy of personal identity rather than personhood.